Fostering a Love for Arabic through Digital Media: Developing a Communicative Dictionary Prototype for Islamic Elementary School Students - Ahmad Syadzili; Mohammad Ahsanuddin; Moch. Wahib Dariyadi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The low interest of Madrasah Ibtidaiyah (Islamic Elementary School) students in learning Arabic often stems from the use of static and non-functional learning media. This research aims to develop a communicative digital dictionary prototype specifically designed to foster an early affinity for the Arabic language, aligned with the